Perovskite solar cell and preparation method and application thereof

By using a composite hole transport structure of nickel oxide layer and SAM organic modification layer in perovskite solar cells, the problem of high energy loss in hole transport layer interface in trans perovskite solar cells is solved, and the conversion efficiency of the device is improved and stability, achieving more efficient hole transmission.

CN119173047AActive Publication Date: 2024-12-20SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411185507.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-20
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

The high energy loss and low hole transmission efficiency of the hole transport layer interface in trans perovskite solar cells hinder the improvement of device performance and high efficiency development.

Method used

The composite hole transport structure of the nickel oxide layer and the bimodal SAM organic modification layer is adopted. Through the synergistic effect of SAM self-assembly and the nickel oxide layer, interface passivation, energy level matching and hole extraction are achieved, and hole transmission efficiency is improved.

Benefits of technology

The conversion efficiency, open circuit voltage, fill factor and short circuit current of perovskite solar cells are significantly improved, the stability and performance of the device are enhanced, and the preparation process is simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173047A_ABST
    Figure CN119173047A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite solar cell and a preparation method and application thereof, and belongs to the technical field of photovoltaics. The perovskite solar cell provided by the invention comprises a transparent electrode, a composite hole transport structure, a perovskite absorption layer, an electron transport layer and a metal electrode which are sequentially stacked, the composite hole transport structure comprises a nickel oxide layer and an SAM organic modification layer which are stacked from the transparent electrode; the preparation raw material of the SAM organic modification layer comprises a mixture formed by Me-4PACz and Br-4PACz according to the molar ratio of (0.25-10): 1. According to the perovskite solar cell provided by the invention, the technical parameters such as PCE, VOC, FF and JSC of the perovskite solar cell can be effectively improved. The invention also provides a preparation method and application of the perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of photovoltaic technology, and in particular to a perovskite solar cell and a preparation method and application thereof. Background Art

[0002] With the rapid advancement of science and technology, human society's demand for energy is increasing. However, the reserves of traditional fossil energy are limited, and the use of traditional fossil energy will cause environmental pollution, which limits its further development. Therefore, the development of new clean and renewable energy has become a top priority. In the process of developing renewable energy, solar cells have received widespread attention as a sustainable clean energy conversion technology. Among various types of solar cells, perovskite solar cells (PSCs) have made significant progress in recent years. Thanks to its excellent photovoltaic performance and low cost, PSC is considered to be one of the main competitors in the next generation of photovoltaic industry. Among them, the trans-structured PSC has become a research hotspot due to its process superiority, low hysteresis effect and high stability. At present, the highest certified efficiency of the trans-PSC has exceeded 26.7%, exceeding the traditional structure PSC.

[0003] The rapid development of trans-PSCs is due to the in-depth study of the action mechanism of its key materials. In PSCs, the study of transport layer materials and their action mechanisms is crucial to improving the power conversion efficiency (PCE) of devices. The research on transport layer materials not only focuses on their intrinsic transport properties, but also includes the suppression of interface transmission losses, so it often involves the regulation of multiple complex mechanisms and processes.

[0004] Since the inverse PSC adopts a pin structure, the hole transport layer (HTL) is buried in the perovskite layer as the lower interface and participates in the light absorption process of the perovskite film. Therefore, compared with the upper electron transport layer (ETL), the HTL has a more critical impact on the photovoltaic performance of the device. Although there are many HTLs such as organic molecules or polymers (PTAA), metal oxide semiconductors (NiO X ) and self-assembled monolayers (SAMs) have been designed and widely used to meet the basic requirements of hole transport. However, these HTLs still have significant problems in long-term stability, intrinsic carrier extraction, and high-efficiency PCE applications. These problems hinder the further application of HTLs and restrict the development of high-efficiency trans-PSCs. Therefore, the development of an efficient transport HTL with strong reliability and high adaptability is of great significance for the long-term development of trans-PSCs. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a perovskite solar cell that can effectively improve its PCE (conversion efficiency), V OC (open circuit voltage), FF (fill factor) and JSC (short-circuit current) and other technical parameters; it solves the technical problems of high interface energy loss and low hole transport efficiency in the related technologies.

[0006] The present invention also provides a method for preparing the perovskite solar cell.

[0007] The present invention also provides applications of the perovskite solar cell.

[0008] According to an embodiment of the first aspect of the present invention, a perovskite solar cell is provided, wherein the perovskite solar cell comprises a transparent electrode, a composite hole transport structure, a perovskite absorption layer, an electron transport layer and a metal electrode which are sequentially stacked; the composite hole transport structure comprises a nickel oxide layer and a SAM organic modification layer which are stacked starting from the transparent electrode;

[0009] The raw materials for preparing the SAM organic modification layer include a mixture of Me-4PACz ([4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, CAS: 2747959-96-0) and Br-4PACz ([4-(3,6-dibromo-9H-carbazole-9-yl)butyl]phosphonic acid; CAS: 2996161-28-3) in a molar ratio of 0.25 to 10:1.

[0010] The perovskite solar cell according to the embodiment of the present invention has at least the following beneficial effects:

[0011] In an inverse perovskite solar cell, interface carrier transport has a great influence on device performance, so the present invention introduces a modifying material (SAM organic modifying layer) to achieve interface passivation and reduce interface transport losses.

[0012] In the composite hole transport structure adopted by the present invention, the structural characteristics of the transmission stability, dense coverage and anchoring uniformity of the nickel oxide layer are utilized, and a bimolecular SAM organic modification layer with interface energy band regulation is loaded at the same time. Under the synergistic effect of the nickel oxide layer and the SAM organic modification layer, on the one hand, good contact and stable transmission between the composite hole structure and the bottom transparent electrode can be guaranteed, and on the other hand, energy level matching and defect passivation between the perovskite absorption layer and the composite hole transport structure can be achieved, bringing additional hole extraction enhancement and composite loss suppression to the interface transmission. Therefore, the obtained composite hole transport structure can effectively improve the hole transport efficiency, and also has the advantages of good stability and simple preparation.

[0013] SAM molecules usually have two main parts: an anchoring group and a functional group. The anchoring group enables the SAM molecule to bind to the surface hydroxyl group (-OH) of the oxide (nickel oxide layer) to achieve its self-assembly arrangement on the oxide surface, and the functional group has the effects of hole transmission and wettability enhancement. The characteristics of self-assembly anchoring and adjustable structure of SAM give it a broad application prospect. It can not only be used as a hole transport material alone, but also can be used as a surface modification of oxides, with the advantages of simple preparation and excellent performance. In the perovskite solar cell provided by the present invention, since a SAM organic modification layer of special material and proportion is selected, it can not only stabilize the nickel oxide layer structure, but also make the energy band of the composite hole transport structure adjustable, which is more conducive to forming an energy level match with the perovskite absorption layer, avoiding the energy loss caused by energy level mismatch; and finally improving the comprehensive performance of the perovskite solar cell.

[0014] According to some embodiments of the present invention, the perovskite solar cell further comprises a transparent substrate disposed on a side of the transparent electrode away from the composite hole transport structure. In industry, for the convenience of manufacturing and transportation, the transparent substrate and the transparent electrode are usually combined to form an integral component, such as an integral ITO glass, etc.; the ITO layer in the ITO glass is produced by magnetron sputtering; wherein the transparent electrode acts as a positive electrode.

[0015] According to some embodiments of the present invention, the nickel oxide layer includes nickel oxide (NiO X ) nanoparticles. Wherein, the nickel oxide nanoparticles have a cubic lattice structure.

[0016] Inorganic NiO X Due to the non-stoichiometric coordination environment of its preparation process, there are multiple components composed of Ni with different valence states, such as NiO, NiOOH, Ni(OH)2 and Ni ≥3+ , these components make the nickel oxide layer conducive to hole transport. In addition, NiO X The surface hydroxyl groups (-OH) of NiO also make it a good anchoring point for specific groups. X It also has the advantages of low temperature processing, low cost and good stability.

[0017] According to some embodiments of the present invention, the thickness of the nickel oxide layer is 25-35 nm, for example, about 30 nm.

[0018] According to some embodiments of the present invention, the molar ratio of Me-4PACz to Br-4PACz is 0.25 to 9:1, for example, about 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1 or about 8:1.

[0019] According to some embodiments of the present invention, the molar ratio of Me-4PACz to Br-4PACz is 8 to 10:1, for example, about 9:1.

[0020] By adjusting the above ratio, the composite hole transport structure can have different energy band structures, and further can be adapted to the energy levels of different perovskite absorption layers, which is more conducive to the interface transmission between the perovskite absorption layer and the composite hole transport structure.

[0021] According to some embodiments of the present invention, the thickness of the SAM organic modification layer is 0.5 to 1.5 nm. For example, it can be about 1 nm. In fact, the organic modification layer is usually a molecular layer of at least a few layers, and its thickness is difficult to effectively measure. The thickness is calculated based on the amount of raw materials used in the preparation of the SAM organic modification layer.

[0022] According to some embodiments of the present invention, the material formula of the perovskite absorption layer is (Cs x FA y MA 1-x-y )Pb(I z Br 3-z ).

[0023] According to some embodiments of the present invention, the perovskite absorption layer includes at least one of a high-efficiency antisolvent perovskite, a high-efficiency antisolvent-free perovskite, and a wide-bandgap perovskite (bandgap 1.85 eV).

[0024] The representative material of the efficient anti-solvent perovskite is Cs 0.05 FA 0.85 MA 0.1 PbI3.

[0025] The representative material of the high-efficiency anti-solvent-free perovskite is Cs 0.17 FA 0.83 PbI3.

[0026] The wide bandgap perovskite representative material is Cs 0.2 FA 0.8 PbI 1.5 Br 1.5 .

[0027] In actual production, the subscripts in the chemical formula of the above material can change according to the change of feed ratio, and the efficiency of perovskite will change accordingly.

[0028] According to some embodiments of the present invention, the material of the perovskite absorption layer includes Cs 0.05 FA 0.85 MA 0.1 PbI3、Cs 0.17 FA 0.83PbI3 and Cs 0.2 FA 0.8 PbI 1.5 Br 1.5 At least one of. Specifically,

[0029] When the material of the perovskite absorption layer is Cs 0.05 FA 0.85 MA 0.1 When PbI3 is used, the molar ratio of Me-4PACz to Br-4PACz in the SAM organic modification layer is 4 to 10:1, for example, about 5:1, 6:1, 8:1 or about 9:1.

[0030] When the material of the perovskite absorption layer is Cs 0.17 FA 0.83 When PbI3 is used, the molar ratio of Me-4PACz to Br-4PACz in the SAM organic modification layer is 3.5-4.5:1.

[0031] When the material of the perovskite absorption layer is Cs 0.2 FA 0.8 PbI 1.5 Br 1.5 When the molar ratio of Me-4PACz to Br-4PACz in the SAM organic modification layer is 0.8-1.2:1.

[0032] According to some embodiments of the present invention, the thickness of the perovskite absorption layer is 700-750 nm, for example, about 720 nm or about 730 nm.

[0033] According to some embodiments of the present invention, the perovskite solar cell further comprises an upper surface passivation layer disposed between the perovskite absorption layer and the electron transport layer.

[0034] According to some embodiments of the present invention, the material of the upper surface passivation layer includes piperazine monoiodide (PI, CAS: 56310-12-4). The upper surface passivation layer is generally considered to be embedded in the perovskite active layer, and the thickness is negligible.

[0035] According to some embodiments of the present invention, the material of the electron transport layer includes fullerene (C 60 , CAS: 99685-96-8) and bathocuproine (BCP, CAS: 4733-39-5).

[0036] According to some embodiments of the present invention, the electron transport layer includes a fullerene layer and a bathocuproin layer stacked together. The thickness of the fullerene layer is 35 to 45 nm, for example, about 40 nm. The thickness of the bathocuproin layer is 5 to 10 nm, for example, about 8 nm.

[0037] According to some embodiments of the present invention, the perovskite solar cell further includes a hole blocking layer disposed between the electron transport layer and the metal electrode.

[0038] According to some embodiments of the present invention, the metal electrode is made of copper (serving as a negative electrode).

[0039] According to some embodiments of the present invention, the thickness of the metal electrode is 80-120 nm, for example, about 100 nm.

[0040] According to an embodiment of the second aspect of the present invention, a method for preparing the perovskite solar cell is provided, the method comprising the following steps:

[0041] S1. Disposing the nickel oxide layer on the surface of the transparent electrode;

[0042] S2. The SAM organic modification layer is disposed on the surface of the nickel oxide layer;

[0043] S3. sequentially arrange the perovskite absorption layer, the electron transport layer and the metal electrode on the surface of the SAM organic modification layer.

[0044] Since the preparation method adopts all the technical solutions of the perovskite solar cell in the above embodiment, it at least has all the beneficial effects brought by the technical solutions in the above embodiment.

[0045] The preparation method provided by the present invention has the advantages of being simple and easy to operate and implement, can promote the large-scale production of perovskite solar cells, and has good application prospects.

[0046] According to some embodiments of the present invention, in step S1, the nickel oxide layer is provided by sequentially performing a first spin coating and a first annealing.

[0047] According to some embodiments of the present invention, the first spin coating method includes at least one of dynamic spin coating and static spin coating, preferably static spin coating.

[0048] According to some embodiments of the present invention, the slurry used for the first spin coating is a nickel oxide dispersion, and the solvent of the nickel oxide dispersion includes water.

[0049] According to some embodiments of the present invention, the solvent of the nickel oxide dispersion is a mixture of water and isopropanol.

[0050] According to some embodiments of the present invention, in the solvent of the nickel oxide dispersion, the volume ratio of water to isopropanol is 3 to 5:1; for example, it may be about 3.5:1, 4:1 or about 4.5:1.

[0051] According to some embodiments of the present invention, the concentration of the nickel oxide dispersion is 5 to 15 mg / mL; for example, it can be about 8 mg / mL, 10 mg / mL or about 12 mg / mL. In the first spin coating, the concentration will affect the thickness of the nickel oxide layer to a certain extent, and the thickness will affect the hole transport efficiency of the nickel oxide layer; within this concentration range, the hole transport capacity is not limited and will not hinder the incidence of sunlight.

[0052] According to some embodiments of the present invention, in the first spin coating, the amount of the nickel oxide dispersion is 25-45 μL / cm 2 For example, it can be about 30 μL / cm 2 , 35μL / cm 2 or about 40 μL / cm 2 .

[0053] According to some embodiments of the present invention, the rotation speed of the first spin coating is 3000-4000 rpm. For example, it can be about 3500 rpm. Within this rotation speed, the thickness uniformity of the nickel oxide layer can be improved, and the nickel oxide layer can have a suitable thickness.

[0054] According to some embodiments of the present invention, the duration of the first spin coating is 30 to 50 seconds, for example, about 35 seconds, 40 seconds or about 45 seconds.

[0055] According to some embodiments of the present invention, the temperature of the first annealing is 105-115° C., for example, specifically about 100° C.

[0056] According to some embodiments of the present invention, the duration of the first annealing is 10 minutes to 15 minutes, for example, about 12 minutes or about 13 minutes.

[0057] According to some embodiments of the present invention, in step S2, the SAM organic modification layer is provided by sequentially performing a second spin coating and a second annealing.

[0058] The present invention forms a composite hole transport structure by two spin coatings, and can make two molecules in the SAM organic modification layer self-assemble and anchor on the inorganic transport layer, which has the advantages of simple method and high repeatability.

[0059] According to some embodiments of the present invention, the second spin coating method includes at least one of dynamic spin coating and static spin coating, preferably static spin coating.

[0060] According to some embodiments of the present invention, in the slurry used for the second spin coating, the solvent is at least one of an alcohol solvent, DMF and DMSO; the solute is Me-4PACz and Br-4PACz. The alcohol solvent includes at least one of isopropyl alcohol (IPA), methanol and ethanol.

[0061] According to some embodiments of the present invention, the concentration of the solute in the slurry used for the second spin coating is 0.8-1.5 mmol / L, for example, about 1 mmol / L or about 1.2 mmol / L.

[0062] According to some embodiments of the present invention, in the second spin coating, the amount of slurry used is 25-45 μL / cm 2 For example, it can be about 30 μL / cm 2 , 35μL / cm 2 or about 40 μL / cm 2 According to some embodiments of the present invention, the second spin coating has a rotation speed of 3000-5000 rpm, for example, about 4000 rpm.

[0063] According to some embodiments of the present invention, the duration of the second spin coating is 25 to 35 seconds, for example, about 30 seconds.

[0064] Like the first spin coating, the concentration of the slurry used in the second spin coating, the rotation speed and duration of the spin coating, etc., all have the function of adjusting the thickness and thickness uniformity of the SAM organic modification layer.

[0065] According to some embodiments of the present invention, the temperature of the second annealing is 100-110° C., for example, about 105° C.

[0066] According to some embodiments of the present invention, the duration of the second annealing is 10 to 15 minutes, for example, about 12 minutes.

[0067] According to some embodiments of the present invention, in step S3, the provision of the perovskite active layer comprises the following steps:

[0068] According to the stoichiometric ratio of ABX3, AX and BX2 are mixed in an organic solvent to obtain a perovskite precursor slurry;

[0069] The perovskite precursor slurry is spin-coated on the surface of the composite hole transport structure and annealed for the third time.

[0070] in,

[0071] AX comprises at least one of MACl, CsI, MAI and FAI;

[0072] BX2 includes at least one of PbI2, PbCl2 and PbBr2.

[0073] Which of AX and BX2 to choose and how much to add is determined based on the target material of the perovskite active layer.

[0074] Due to errors in material feeding, a deviation of the subscript value within the range of ±2% in the chemical formula of the material of the perovskite active layer is acceptable.

[0075] The organic solvent is a mixture of DMF and DMSO, wherein the volume ratio of DMF to DMSO is 3 to 5:1, for example, about 3.5:1, 4:1 or about 4.5:1.

[0076] The concentration of the perovskite precursor slurry is 1-2 mol / L based on ABX3; for example, it can be about 1.2 mol / L, 1.5 mol / L, 1.6 mol / L or about 1.8 mol / L.

[0077] The spin coating amount of the precursor slurry is 25-45 μL / cm 2 For example, it can be about 30 μL / cm 2 , 35μL / cm 2 or about 40 μL / cm 2 .L / cm 2 For example, it can be about 60 μL / cm 2 , 70μL / cm 2 , 80μL / cm 2 or about 90 μL / cm 2 .

[0078] The temperature of the third annealing is 90-160° C., for example, about 100° C., 110° C., 140° C. or about 150° C.

[0079] The duration of the third annealing is 10 to 35 minutes, for example, about 15 minutes, 20 minutes, 25 minutes or about 30 minutes.

[0080] According to some embodiments of the present invention, step S3 further includes disposing the upper surface passivation layer between the perovskite active layer and the electron transport layer.

[0081] The method for setting the upper surface passivation layer includes spin coating the PI solution on the surface of the perovskite active layer and performing a fourth annealing.

[0082] The concentration of the PI solution is 0.3-0.8 mg / mL; for example, it can be about 0.5 mg / mL.

[0083] The solvent of the PI solution includes isopropanol.

[0084] The dosage of the PI solution is 25-45 μL / cm 2 For example, it can be about 30 μL / cm 2 , 35μL / cm 2 or about 40 μL / cm 2 The PI solution is spin-coated at a rotation speed of 4500 to 5500 rpm, for example, about 5000 rpm.

[0085] The spin coating of the PI solution takes 25 to 35 seconds, for example, about 30 seconds.

[0086] The temperature of the fourth annealing is 90-110° C., for example, specifically about 100° C.

[0087] The duration of the fourth annealing is 3 to 8 minutes; for example, it may be about 5 minutes.

[0088] According to some embodiments of the present invention, in step S3, the method for providing the electron transport layer and the metal electrode comprises vacuum evaporation.

[0089] The vacuum degree required for vacuum evaporation is about 4×10 -5 Torr.

[0090] The rate of vacuum evaporation is For example, it can be about

[0091] Unless otherwise specified, the spin coating mentioned in the present invention can be performed using a desktop coating machine, and the annealing can be performed using a temperature-controlled heating table. However, the present invention does not impose strict restrictions on the instrument, and in actual production, appropriate equipment can be selected for testing according to experimental requirements and experimental conditions.

[0092] According to an embodiment of the third aspect of the present invention, there is provided an application of the perovskite solar cell in terrestrial photovoltaics, space photovoltaics or wearable devices.

[0093] Since the application adopts all the technical solutions of the perovskite solar cell of the above-mentioned embodiment, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiment.

[0094] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.

[0095] Unless otherwise specified, “between” in the present invention includes the number itself, for example, “between 2 and 3” includes the endpoint values ​​2 and 3.

[0096] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0097] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0098] Figure 1 It is a schematic diagram of the structure of a perovskite solar cell prepared according to an embodiment of the present invention.

[0099] Figure 2 is a KPFM image of the nickel oxide layer obtained in step S1 of Example 1 of the present invention;

[0100] Figure 3 is a KPFM image of the SAM organic modification layer obtained in step S2 of Example 1 of the present invention;

[0101] Figure 4 It is a band structure diagram of the components obtained in steps S1, S2 and S3 of Example 1 of the present invention.

[0102] Figure 5 It is a diagram of the energy band structure of the components obtained in steps S2 and S3 of embodiments 1 to 3 of the present invention.

[0103] Figure 6 These are the performance statistics of the perovskite solar cells obtained from Example 1, Examples 4 to 6, Comparative Examples 1 to 2 and Comparative Example 4 of the present invention.

[0104] Figure 7 These are the performance statistics of the perovskite solar cells obtained in Example 1, Comparative Example 1, and Comparative Examples 3 to 4 of the present invention.

[0105] Figure 8 3 and 4. These are the JV curves of the perovskite solar cells obtained in Example 1 of the present invention and Comparative Example 4.

[0106] Fig. 9 3 and 4 are JV curves of the perovskite solar cells obtained in Example 2 of the present invention and Comparative Example 5.

[0107] Fig.10 3 and 6 are JV curves of the perovskite solar cells obtained in Example 3 of the present invention and Comparative Example 6. DETAILED DESCRIPTION

[0108] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0109] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0110] Example 1

[0111] refer to Figure 1 In this example, a perovskite solar cell is prepared. The specific steps are as follows:

[0112] S1. Prepare NiO with a concentration of 10 mg / mL X Dispersion liquid, solvent is water:IPA=4:1 (volume ratio).

[0113] Add 60 μL of NiO X The dispersion was dripped onto the surface of the ITO layer on the cleaned ITO glass (composite structure of transparent substrate and transparent electrode, size 1.5 cm × 1.5 cm), and the static spin coating method (first spin coating) was used to spin coat at 3000 rpm for 40 seconds. The wet film was then transferred to a 110°C constant temperature heating table for 15 minutes of annealing (first annealing) to obtain a nickel oxide layer with a thickness of about 30 nm.

[0114] The NiO used in this step X Purchased from Liaoning Youxuan New Energy Technology Co., Ltd., purity: 99.999%.

[0115] S2. Mix the IPA solutions of Me-4PACz and Br-4PACz of the same concentration of 1mmol / L in a volume ratio of 9:1 to obtain the slurry for the second spin coating. Drop 60μL of the slurry for the second spin coating on the surface of the nickel oxide layer, and use the static spin coating method (second spin coating) to spin at 5000rpm for 30s. Then transfer the wet film to a 100℃ constant temperature heating table for annealing for about 10min (second annealing) to obtain a SAM organic modification layer with a thickness of about 1nm, completing the preparation of the composite hole transport structure.

[0116] S3. sequentially arrange a perovskite absorption layer, an upper surface passivation layer, an electron transport layer and a metal electrode on the surface of the SAM organic modification layer.

[0117] S3a. Setup of perovskite absorber layer:

[0118] According to the chemical formula Cs 0.05 FA 0.85 MA 0.1 The ratio of MACl, CsI, MAI, FAI, and PbI3 (hereinafter referred to as Formula I) was adjusted, MACl, CsI, MAI, FAI, and PbI2 were mixed in a DMF:DMSO mixed solvent (4:1 volume ratio), and then oscillated and stirred for more than 2 hours until transparent, and the resulting slurry was filtered using a 0.22 μm PTFE filter membrane to form a 1.6 mol / L (based on Formula I and feed amount) perovskite precursor slurry.

[0119] 60 μL of perovskite precursor slurry was dripped onto the composite hole transport structure, and then the static spin coating method was used to spin-coat at a low speed of 1000 rpm for 5 seconds and then at a high speed of 5000 rpm for 30 seconds. About 200 μL of CB anti-solvent was dynamically dripped at the 18th to 19th second of the high speed. The resulting wet film was then transferred to a 100°C constant temperature heating table for annealing for about 30 minutes to obtain a perovskite absorption layer with a thickness of about 720 nm.

[0120] S3b. Setting of top surface passivation layer:

[0121] Prepare a PI solution with a concentration of 0.5 mg / mL, and the solvent is IPA. Use the dynamic spin coating method to spin-coat at a speed of 5000 rpm for 30 seconds to spin-coat 60 μL of the PI solution on the perovskite absorption layer to form a film. Then transfer the wet film to a 100°C constant temperature heating table for annealing for about 5 minutes to obtain the upper surface passivation layer.

[0122] S3c. Setup of electron transport layer and metal electrode:

[0123] The component obtained in step S3b is mounted on the designed evaporation mask and fixed in the chamber of the vacuum evaporation apparatus. -5 Torr conditions, 40 nm of C was sequentially deposited by thermal evaporation at an evaporation rate of 60 , 8nm BCP and 100nm Cu to complete the preparation of perovskite solar cells.

[0124] The effective area of ​​the perovskite solar cell obtained in this example is 0.1 cm 2 .

[0125] Example 2

[0126] This example prepares a perovskite solar cell, and the specific process is different from that of Example 1 in that:

[0127] In step S2, the volume ratio of Me-4PACz to Br-4PACz in IPA solution is 8:2;

[0128] The operation of step S3a is:

[0129] According to the chemical formula Cs 0.17 FA 0.83 The ratio of CsI, FAI, PbI2 and PbCl2 was adjusted, and CsI, FAI, PbI2 and PbCl2 were mixed in a DMF:DMSO mixed solvent (5:1 volume ratio), and then oscillated and stirred for more than 2 hours until transparent, and the obtained slurry was filtered using a 0.22μm PTFE filter membrane to form a 2mol / L (based on Formula II and feed amount) perovskite precursor slurry.

[0130] 60 μL of perovskite precursor slurry was dropped onto the composite hole transport structure and spun at 5000 rpm for 40 seconds using a static spin coating method. The resulting wet film was then transferred to a 150°C constant temperature heating table for annealing for about 10 minutes to obtain a perovskite absorption layer.

[0131] Example 3

[0132] This example prepares a perovskite solar cell, which differs from Example 1 in that:

[0133] In step S2, the volume ratio of Me-4PACz to Br-4PACz in IPA solution is 5:5;

[0134] The operation of step S3a is:

[0135] According to the chemical formula Cs 0.2 Fa 0.8 PbI 1.5 Br 1.5(hereinafter referred to as Formula III), CsI, MAI, FAI, PbI2 and PbBr2 were mixed in a DMF:DMSO mixed solvent (3:1 volume ratio), and then oscillated and stirred for more than 2 hours until transparent, and the resulting slurry was filtered using a 0.22μm PTFE filter membrane to form a 1.2mol / L (based on Formula II and feed amount) perovskite precursor slurry.

[0136] 60 μL of perovskite precursor slurry was dripped onto the composite hole transport structure, and then the static spin coating method was used to spin-coat at a low speed of 1000 rpm for 2 seconds and then at a high speed of 3000 rpm for 40 seconds. At the 28th to 29th second of the high speed, about 200 μL of CB anti-solvent was dynamically dripped. The resulting wet film was then transferred to a 100°C constant temperature heating table for annealing for about 15 minutes to obtain a perovskite film.

[0137] Example 4

[0138] This example prepares a perovskite solar cell, which differs from Example 1 in that:

[0139] In step S2, the volume ratio of the IPA solution of Me-4PACz to Br-4PACz is 8:2.

[0140] Example 5

[0141] This example prepares a perovskite solar cell, which differs from Example 1 in that:

[0142] In step S2, the volume ratio of the IPA solution of Me-4PACz to that of Br-4PACz is 5:5.

[0143] Example 6

[0144] This example prepares a perovskite solar cell, which differs from Example 1 in that:

[0145] In step S2, the volume ratio of the IPA solution of Me-4PACz to Br-4PACz is 2:8.

[0146] Comparative Example 1

[0147] This example prepares a perovskite solar cell, which differs from Example 1 in that:

[0148] The operation of step S2 is:

[0149] 60 μL of 1 mmol / L Me-4PACz IPA solution was dropped onto the surface of the nickel oxide layer and spun at 5000 rpm for 30 seconds using a static spin coating method. The wet film was then transferred to a 100°C constant temperature heating table for annealing for about 10 minutes to obtain a dry film of a single molecule SAM organic modification layer, completing the preparation of a composite hole transport structure.

[0150] Comparative Example 2

[0151] This example prepares a perovskite solar cell, which differs from Example 1 in that:

[0152] The operation of step S2 is:

[0153] 60 μL of 1 mmol / L Br-4PACz IPA solution was dropped onto the surface of the nickel oxide layer and spun at 5000 rpm for 30 seconds using a static spin coating method. The wet film was then transferred to a 100°C constant temperature heating table for annealing for about 10 minutes to obtain a dry film of a single molecule SAM organic modification layer, completing the preparation of a composite hole transport structure.

[0154] Comparative Example 3

[0155] This example prepares a perovskite solar cell, which differs from Example 1 in that:

[0156] The operation of step S2 is:

[0157] 60 μL of 1 mmol / L 2PACz (CAS: 20999-38-6) IPA solution was dropped onto the surface of the nickel oxide layer and spun at 5000 rpm for 30 seconds using a static spin coating method. The wet film was then transferred to a 100°C constant temperature heating table for annealing for about 10 minutes to obtain a dry film of a single molecule SAM organic modification layer, completing the preparation of a composite hole transport structure.

[0158] Comparative Example 4

[0159] This example prepares a perovskite solar cell, which differs from Example 1 in that:

[0160] Step S2 is not included, that is, the perovskite active layer is directly deposited on the surface of the nickel oxide layer.

[0161] Comparative Example 5

[0162] This example prepares a perovskite solar cell, which differs from Example 2 in that:

[0163] Step S2 is not included, that is, the perovskite active layer is directly deposited on the surface of the nickel oxide layer.

[0164] Comparative Example 6

[0165] This example prepares a perovskite solar cell, which differs from Example 3 in that:

[0166] Step S2 is not included, that is, the perovskite active layer is directly deposited on the surface of the nickel oxide layer.

[0167] Test Example 1

[0168] In this example, the morphology of the nickel oxide layer obtained in step S1 of Example 1 and the SAM organic modified layer obtained in step S2 were tested by Kelvin probe force microscopy (KPFM). The results showed that compared with the pure nickel oxide layer, the sample with the SAM organic modified layer spun on showed a significant negative shift in surface potential (see scale), indicating that the composite hole transport structure with the SAM organic modified layer showed a more p-type band structure, which is conducive to interface hole transport. The specific results are as follows: Figures 2-3 shown.

[0169] Test Example 2

[0170] This example calculates the band structure of the components obtained in steps S1 to S3a of Examples 1 to 3. The results show:

[0171] In Example 1, the energy bands of the nickel oxide layer and the perovskite layer are mismatched. However, by adding a SAM organic modification layer with a suitable composition ratio, the energy bands of the composite hole transport structure and the perovskite layer are matched, thereby significantly reducing the energy loss caused by the energy level mismatch. Figure 4 As shown in the figure, ET-HTL-10% represents the SAM organic modification layer of Example 1, E CBM Indicates the conduction band bottom (conduction band minimum), E F represents the Fermi level, E VBM represents the top of the valence band, and Evac represents the vacuum energy level.

[0172] In Example 2 and Example 3, by setting a SAM organic modification layer, the energy band matching of the composite hole transport structure and the perovskite layer is also improved to a certain extent; however, as can be seen from the figure, it is not completely matched. In actual production, by adjusting the molar ratio of Me-4PACz to Br-4PACz in the SAM organic modification layer, a SAM organic modification layer with a higher energy band matching degree can be obtained for a specific perovskite active layer, thereby obtaining a perovskite solar cell with better comprehensive performance. Figure 5 As shown, ET-HTL-20% represents Example 2, and ET-HTL-50% represents Example 3.

[0173] Test Example 3

[0174] The current-voltage characteristic curve (JV) is an important indicator of the performance of photovoltaic cell devices. Through the JV test, the open circuit voltage (V OC ) and short-circuit current (J SC ), and combined with the maximum power point (MPP) to calculate the fill factor (FF) of the device, further obtain the power conversion efficiency (PCE) of the perovskite solar cell to measure its ability to utilize sunlight.

[0175] This example tests the current-voltage characteristic curves of the perovskite solar cells obtained in the examples and comparative examples. The active area tested is 0.0736 cm 2 The JV curves were obtained by forward scanning and reverse scanning in the same bias range with a scanning rate of 0.02 V / s and a scanning step of 20 mV under 1 sun illumination of the AM1.5G spectrum.

[0176] Table 1 JV test parameters of perovskite solar cells obtained in Examples 1 to 6 and Comparative Examples 1 to 6

[0177]

[0178] From the comparison of the results of Examples 1 to 3 and Comparative Examples 4 to 6, it can be seen that the present invention sets a composite hole transport structure containing a SAM organic modification layer in the perovskite solar cell, and by adjusting the ratio of Me-4PACz to Br-4PACz therein, a good energy level matching with a variety of perovskite active layers can be achieved, and the prepared inverse perovskite solar cell has a significantly improved device open circuit voltage and fill factor effect compared to the traditional single inorganic transport layer structure (Comparative Examples 4 to 6), indicating that the composite hole transport structure effectively suppresses interface losses and significantly enhances hole extraction; specifically, the corresponding embodiment has a PCE improvement ratio of ≥8% over the comparative example; for example, it can reach 10%, 11% or even 12%. The test results of Examples 1 to 3 and Comparative Examples 4 to 6 are summarized in Table 1. The test results of Example 1 and Comparative Example 4 are shown in Table 1. Figure 8 As shown in the figure, NiO x ET-HTL-10% represents comparative example 4, and ET-HTL-10% represents embodiment 1. The test results of embodiment 2 and comparative example 5 are as follows: Fig. 9 As shown in the figure, NiO x ET-HTL-20% represents comparative example 5, and ET-HTL-20% represents embodiment 2. The test results of embodiment 3 and comparative example 6 are as follows: Fig.10 As shown in the figure, NiO x represents Comparative Example 6, and ET-HTL-50% represents Example 3. Figures 8 to 10 In the figure, Forward scan represents the positive scan curve, Reverse scan represents the negative scan curve, and the vertical coordinate Current density (JSC ) represents the current density, and the horizontal axis Voltage (V OC ) represents the open circuit voltage.

[0179] The comparison between the results of Example 1 and Comparative Examples 1 to 4 shows that there is a significant synergistic effect between Me-4PACz and Br-4PACz in the SAM organic modification layer, which can improve the energy band matching of the composite hole transport structure and the perovskite active layer, and ultimately significantly improve the V OC , FF, J SC and PCE; if the SAM organic modification layer contains only one self-assembling molecule, whether it is Me-4PACz, Br-4PACz, or other self-assembling molecules known in the art, it cannot or cannot effectively improve the comprehensive performance of the obtained perovskite solar cell. The specific test results are as follows Figure 7 As shown in the figure, NiO x Comparative Example 4, NiO x / 2PACz represents comparative example 3, NiO x / Me-4PACz represents Comparative Example 1, and ET-HTL-10% represents Example 1.

[0180] The comparison of the results of Examples 1, 4 to 6 and Comparative Examples 1 to 2 and 4 shows that when the material of the perovskite active layer is certain, the ratio of Me-4PACz to Br-4PACz in the SAM organic modification layer has an optimal value. For example, when the material of the perovskite active layer is Cs 0.05 FA 0.85 MA 0.1 When PbI3, Me-4PACz:Br-4PACz=9:1 is the best ratio, at which the comprehensive performance of the perovskite solar cell is optimal. If the ratio deviates from the optimal ratio (Examples 4 to 6), the comprehensive performance of the perovskite solar cell will be reduced to a certain extent. In addition, it should be noted that the comprehensive performance of the perovskite solar cell is mainly affected by the selection of materials for its perovskite active layer. The composite hole transport structure can only produce a certain degree of improvement on the basis of the performance of the existing perovskite active layer; that is, if the material of the perovskite active layer is different, there is almost no comparability between the performance of the perovskite solar cell. The specific test results are statistically shown as follows: Figure 6 As shown in the figure, NiO x represents comparative example 4, 10:0 represents comparative example 1, 9:1 represents embodiment 1, 8:2 represents embodiment 4, 5:5 represents embodiment 5, 2:8 represents embodiment 6, and 0:10 represents comparative example 2.

[0181] In summary, the interface enhancement of the composite hole transport structure is of great significance in perovskite solar cells, and the suppression of interface loss and the improvement of hole transport efficiency play a decisive role in improving the performance of perovskite solar cells. In perovskite solar cells, interface loss mainly comes from energy level mismatch and defect capture. Therefore, the present invention reasonably designs the composite hole transport structure to have a more matched energy band structure and a lower defect level, which significantly improves the hole extraction efficiency of the perovskite solar cell and improves the performance of the perovskite solar cell. It is precisely because of the above-mentioned excellent characteristics that the obtained perovskite solar cell is expected to be widely used in the fields of surface photovoltaics, space photovoltaics and wearables.

[0182] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A perovskite solar cell, comprising a transparent electrode, a composite hole transport structure, a perovskite absorption layer, an electron transport layer and a metal electrode which are sequentially stacked; characterized in that: The composite hole transport structure includes a nickel oxide layer and a SAM organic modification layer stacked and arranged starting from the transparent electrode; The raw material for preparing the SAM organic modification layer includes a mixture of Me-4PACz and Br-4PACz in a molar ratio of 0.25 to 10:

1.

2. The perovskite solar cell according to claim 1, characterized in that: The molar ratio of Me-4PACz to Br-4PACz is 8 to 10:

1.

3. The perovskite solar cell according to claim 1, characterized in that: The material formula of the perovskite absorption layer is (Cs x FA y MA 1-x-y )Pb(I z Br 3-z ); and / or, the material of the perovskite absorption layer includes Cs 0.05 FA 0.85 MA 0.1 PbI3、Cs 0.17 FA 0.83 PbI3 and Cs 0.2 FA 0.8 PbI 1.5 Br 1.5 At least one of .

4. The perovskite solar cell according to any one of claims 1 to 3, characterized in that: The perovskite solar cell also includes an upper surface passivation layer disposed between the perovskite absorption layer and the electron transport layer.

5. A method for preparing a perovskite solar cell according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: S1. Disposing the nickel oxide layer on the surface of the transparent electrode; S2. The SAM organic modification layer is disposed on the surface of the nickel oxide layer; S3. sequentially arrange the perovskite absorption layer, the electron transport layer and the metal electrode on the surface of the SAM organic modification layer.

6. The preparation method according to claim 5, characterized in that: In step S1, the nickel oxide layer is provided by sequentially performing a first spin coating and a first annealing.

7. The preparation method according to claim 6, characterized in that: The slurry used for the first spin coating is a nickel oxide dispersion, and the solvent of the nickel oxide dispersion includes water; and / or the temperature of the first annealing is 105-115°C.

8. The preparation method according to claim 5, characterized in that: In step S2, the SAM organic modification layer is provided by sequentially performing a second spin coating and a second annealing.

9. The preparation method according to claim 8, characterized in that: In the slurry used for the second spin coating, the solvent is at least one of an alcohol solvent, DMF and DMSO; the solute is Me-4PACz and Br-4PACz; and / or the temperature of the second annealing is 100-110°C.

10. Use of the perovskite solar cell according to any one of claims 1 to 4 in terrestrial photovoltaics, space photovoltaics or wearable devices.

Citation Information

Patent Citations

  • Perovskite thin film, preparation method thereof and hole transport layer-free p-i-n type perovskite device

    CN116156983A

  • Crystalline silicon perovskite laminated solar cell and preparation method thereof

    CN116801652A